Evaluating lung cancer screening disparities in an integrated healthcare system: barriers and opportunities - Carmen Javier; Sheng-Fang Jiang; Jenna Philippe; Isabel Arana; Jeffrey B. Velotta; Jeffrey B. Velotta (Frontiers in Oncology)
RationaleThe national average rate of lung cancer screening (LCS) has remained low at roughly 6%, with California’s rate among the lowest at 1% compared to all fifty states.MethodsWe enrolled Kaiser Permanente Northern California (KPNC) patients eligible for LCS per the USPSTF guidelines published in 2013 and 2021, respectively. Annual and overall rates of completed initial low-dose computed tomography of chest (LDCT) were computed from February 2015 to February 2022. Chi-squared tests and multivariable Cox regression assessed the impact of sociodemographic factors.ResultsThe average annual completion rate of initial lung cancer screening over the entire study period was 0.95% per the 2013 USPSTF guidelines. In the year 2022, only 0.69% of all eligible study participants per the 2021 USPSTF guidelines completed lung cancer screening. Chi-squared tests demonstrated differences in the overall proportion of individuals screened across the entire study period stratified by sex and race/ethnicity respectively (2013 USPSTF guidelines; 4.72% Males, 4.29% Females, p = 0.09 for the sex categories and Asian 4.31%, African American 3.89%, Hispanic 3.79%, Other 3.48%, Non-Hispanic White 4.79%, p = 0.02 for the race/ethnicity categories. Multivariate time-to-completion analyses demonstrated statistically significant associations for younger age groups (50-60: HR 1.41, 95% CI 1.21–1.64, p < 0.0001, 61-70: HR 1.95, 95% CI 1.68–2.27, p < 0.0001), male sex (HR 1.17, 95% CI 1.07–1.28, p = 0.0009), and all non-White racial/ethnic groups (Asian: HR 0.73, 95% CI 0.62–0.86, p = 0.0002, African American: HR 0.64, 95% CI 0.53–0.78, p < 0.0001, Hispanic: HR 0.66, 95% CI 0.55–0.80, p < 0.0001, Other: HR 0.75, 95% CI 0.60–0.93, p = 0.0086). Neighborhood Deprivation Index (NDI) quartiles were not significantly associated with initial LDCT completion (HRs 0.93 to 1.04; all p-values > 0.3).ConclusionThis average annual rate of LCS at KPNC was comparable to the statewide average in California. Age 61–70 years old, male sex, and non-Hispanic White race/ethnicity were the strongest and most statistically significant predictors of initial LDCT completion. NDI was not associated with screening uptake. No significant improvement in screening uptake was observed within the first year following the release of the 2021 USPSTF guidelines on LCS.